A case of meningeal myxoid solitary fibrous tumor/hemangiopericytoma with unique NAB2-STAT6 fusion gene and symptomatic intratumoral hemorrhage - Takako Kihara, MD; Yoshitane Tsukamoto, MD, PhD; Tomonari Yabuuchi, MD; Yoshifumi Teramoto, MD; Haruki Yugami, MD; Kimito Yamada, MD; Kazuhiro Nagatsuka, MD; Shohei Matsuo, MD; Seiichi Hirota, MD, PhD (Elsevier, 2017)
We experienced a case of meningeal solitary fibrous tumor (SFT)/hemangiopericytoma (HPC) with symptomatic intratumoral hemorrhage in a 67-year-old Japanese woman. Her chief complaints were sudden onset of motor aphasia and right hemiparesis. Brain computed tomography showed the hemorrhagic mass adjacent to the superior sagittal sinus. The mass was resected and pathological examination of the specimen revealed a tumor that is rich in vessels and accompanied with intratumoral hemorrhage. Short spindle tumor cells were proliferating with myxoid stroma. Tumor cells appeared to be arranged around the vessels and sometimes attached to the vessel wall directly. Although hyalinization of the vessel wall was observed, neither patternless pattern nor staghorn vessels were seen. Immunohistochemistry revealed that the tumor cells were positive for both CD34 and nuclear STAT6. Moreover, gene analyses revealed unique NAB2-STAT6 fusion. Immunohistochemical findings and fusion-gene analyses enabled us to make the definite diagnosis of meningeal myxoid SFT/HPC. The present case showed the three unique features such as clinically symptomatic intratumoral hemorrhage at the onset, rare variant of myxoid SFT/HPC, and unique NAB2-STAT6 fusion. Keyword: Meninx, Myxoid solitary fibrous tumor/hemangiopericytoma, Cerebral hemorrhage, NAB2-STAT6 fusion